2009
DOI: 10.1159/000227280
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Control Study of Single-Pass Albumin Dialysis for Acetaminophen-Induced Acute Liver Failure

Abstract: Background: Extracorporeal support with single-pass albumin dialysis (SPAD) may remove protein-bound toxins in acute liver failure. We evaluated the clinical, physiological and laboratory parameters of SPAD in acetaminophen-induced acute liver failure (AALF). Methods: Retrospective case-control studies of AALF patients were used. Results: We identified 13 AALF patients (6 SPAD-treated, 7 controls). The average age was 38 years, 92% were female, none had cirrhosis and the Model for End-Stage Liver Disease (MELD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 75 publications
0
27
0
2
Order By: Relevance
“…In a retrospective study, MARS and SPAD showed equal efficacy . In ALF, SPAD was well tolerated, but it failed to improve survival and did not change referral to liver transplantation . In a single‐center experience from Germany, SPAD did not have any impact on survival or transplantation rate in patients with ACLF listed for transplantation .…”
Section: Currently Available Elsdsmentioning
confidence: 93%
“…In a retrospective study, MARS and SPAD showed equal efficacy . In ALF, SPAD was well tolerated, but it failed to improve survival and did not change referral to liver transplantation . In a single‐center experience from Germany, SPAD did not have any impact on survival or transplantation rate in patients with ACLF listed for transplantation .…”
Section: Currently Available Elsdsmentioning
confidence: 93%
“…The DCCM has had an interest in kidney dysfunction associated with severe liver disease and has described the use of single pass albumin dialysis, initiated a molecular adsorbent recirculation system program and is evaluating the use of intraoperative CRRT during cadaveric orthotopic liver transplantation [22][23][24] . In addition, the DCCM has recruited an intensivist with training in gastroenterology and hepatology, Dr. Constantine (Dean) Karvellas, thereby opening further opportunities in the investigation and treatment of severe hepatic disease and kidney disease associated with liver failure.…”
Section: Critical Care Nephrology At the Uofa Edmontonmentioning
confidence: 99%
“…In the patient with hemodynamic instability, CRRT is the modality of choice to clear exogenous intoxications. In addition, single-pass albumin dialysis and molecular adsorbent recirculation system can be performed to remove toxins which are highly proteinbound and do not have a very large volume of distribution such as carbamazepine, methotrexate, phenytoin, and acetaminophen [51][52][53][54][55][56]. As opposed to AKI, patients receiving dialysis for the treatment of an acute intoxication typically require a dialysis fluid or replacement fluid with therapeutic concentrations of phosphorus and potassium to avoid electrolyte abnormalities [48].…”
Section: Rrt For "Nonrenal" Indications Intoxicationsmentioning
confidence: 99%